열교저감방식에 따른 진공단열패널이 적용된 벽체의 열교특성분석 - 민다혜(Da-Hye Min); 김상명(Sang-Myung Kim); 김진희(Jin-Hee Kim); 김준태(Jun-Tae Kim) (KIEAE Journal, 2019)
Purpose: The insulation requirements for buildings are being strengthened to make zero energy mandatory. Vacuum insulation panel (VIP) has about 8~10 times better insulation performance than existing insulation and also maintains high insulation performance with a slimmer thickness. However, when VIP is installed on a building wall, thermal bridge occurs. Thermal bridges of VIP itself, thermal bridges due to air gaps between adjacent vacuum insulation panels, and thermal bridges with other building materials that make up the walls. Thermal bridges deteriorate the insulation performance of the building envelope. The purpose of this study is to compare and analyze the insulation performance by designing a wall with vacuum insulation panels and applying a method to improve the insulation performance degradation due to heat bridges. Method: In this paper, thermal bridge phenomenon of the wall was analyzed using Physibel TRISCO simulation program. The walls were designed for VIP encapsulated EPS insulation application walls. The parameters of thermal bridges reduction were set to air gsp seals between VIPs, application of thermal bridge fastener and both. A total of 4 cases were designed. Result: Based on the simulation results thermal bridge effect for wall with encapsulated VIP reduced by 5.2% for Case 1, 7.2% for Case 2, and 13.6% for Case 3. As a result, it was confirmed that the airtight seal between VIPS and the type of connection material affect the thermal bridge of the wall. From the findings in this paper, it is recommended that necessary techniques are adopted to prevent deterioration of insulation performance primarily due to thermal bridges. KCI Citation Count: 2